Réponses

2013-03-24T17:56:30+01:00

EXERCICE 3 :

 

A = (5x - 2)² - (5x - 2)(x - 1)

 

a) 

A = (5x - 2)² - (5x - 2)(x - 1)

A = 25x² - 20x + 4 - 5x² + 5x + 2x - 2

A = 20x² - 13x + 2

 

b)

A = (5x - 2)² - (5x - 2)(x - 1)

A = (5x - 2)[(5x - 2) - (x - 1)]

A = (5x - 2)(5x - 2 - x + 1)

A = (5x - 2)(4x - 1)

 

c)

A = (5x - 2)(4x - 1)

Si x = - 3, alors :

A = (5*(-3) - 2)(4*(-3) - 1)

A = (-15 - 2)(-12 - 1)

A = -17 * (-13)

A = 221

 

C'est pareil pour V2 et 2/5

 

d) 

(5x - 2)(4x - 1) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc :

5x - 2 = 0

5x - 2 + 2 = 0 + 2

5x / 5 = 2 / 5

x = 0,4

 

OU

4x - 1 = 0

4x - 1 + 1 = 0 + 1

4x / 4 = 1 / 4

x = 0,25